2019
DOI: 10.3390/en12081540
|View full text |Cite
|
Sign up to set email alerts
|

The Geographical Distribution and Correlates of Pro-Environmental Attitudes and Behaviors in an Urban Region

Abstract: A lot of emphasis has been put on the densification of urban form to reduce greenhouse gas emissions from transportation. However, many recent studies have found that central urban dwellers, even though their carbon footprints of daily transportation may be lower, might be responsible for higher total emissions than those that reside in suburban areas. Similarly, as with the urban form, higher environmental concern is often considered as an indicator of lower emissions, but several studies have found that pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 84 publications
2
7
0
Order By: Relevance
“…Similarly to Alcock et al [19] and Árnadóttir et al [42], we found pro-environmental attitudes and climate change awareness to predict more flights and a higher GHG load, not less. Defining this as a causal relationship between these two variables would be incorrect, though.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similarly to Alcock et al [19] and Árnadóttir et al [42], we found pro-environmental attitudes and climate change awareness to predict more flights and a higher GHG load, not less. Defining this as a causal relationship between these two variables would be incorrect, though.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the level of GHG emissions from long-distance travel alone reached three tons of CO2e/y per capita, which is more than 50% of the currently available global per capita carbon budget to follow the Intergovernmental Panel on Climate Change (IPCC) pathway to 1.5-degree warming [1]. These findings are in line with those of recent studies of Helsinki in Finland [17,42], although we found slightly lower overall emissions and higher long-distance travel-related emissions in Reykjavik than in Helsinki. For the consistent car-commuters, the overall GHGs from the transport were found to exceed 5.5 t CO2e/y per capita and to transgress the whole current per capita carbon budget without emissions from any other consumption taken into account.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A meta-analysis of 23 studies found the simple existence of sidewalks or footpaths to be the one factor most tightly coupled with walking behaviour (Wang et al 2016 ). Suffice to say, pro-environmental attitudes only matter for travel behaviour insofar as the environment permits acting on them (Árnadóttir et al 2019 ). Of course, the enabling of these pro-environmental behaviours does not guarantee habit formation.…”
Section: Future Outlook: Exploring Habits’ Role In Sustainability Transformationsmentioning
confidence: 99%
“…Exploratory factor analysis is a useful data reduction technique to identify unobserved factors based on multiple observed variables and has been widely used in marketing research [27]. It has also been used in sustainability research to identify some of the most relevant factors using a large number of variables to provide meaningful insights into data, and in particular to examine the attitudes and behaviors surrounding pro-environmental behaviors such as energy conservation [28] and recycling [29], as well as pro-environmental behaviors in general [30]. The authors' literature search revealed no application of exploratory factor analysis for analyzing carbon footprints using microdata to date.…”
mentioning
confidence: 99%